ROAD INFRASTRUCTURE MANAGEMENT - THE PERSPECTIVE OF THE LOCAL ROADS AUTHORITY - Marcin ŚWITAŁA (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents the results of research conducted among 100 local government units performing the duties of road network administrators, i.e., administrators of municipal roads (AMR), county roads (ACR) and those operating within the boundaries of cities with county rights (ACCR). The aim of the research was to identify and assess management problems related to the implementation of statutory measures related to the protection and development of respective road networks. A hypothesis was formulated about the existence of statistically significant differences between the AMR, ACR and ACCR groups, which was verified by quantitative analysis of the data obtained from the online survey. They were analysed and interpreted using the SPSS package and using measures of descriptive statistics, the correlation coefficient and the Kruskal–Wallis test by ranks. The results of the study indicate that the difficulties of providing and maintaining an efficient road network pavement, as well as the challenges of developing draft financing plans for the construction, reconstruction, and rehabilitation of the road network, are currently the main points of focus for all road administrators. The lack of statistical significance of intergroup differences was observed in the vast majority of measurements. The exceptions to this were the differences that occurred in the total number of difficulties reported, which were greater among the members of AMR and ACR than ACCR, as well as the differences related to the implementation of measures undertaken for the maintenance of roadside greenery, which were more onerous for ACR.